Pretreatment with Bifidobacterium longum BAA2573 ameliorates dextran sulfate sodium (DSS)-induced colitis by modulating gut microbiota - Qiong Lin; Qiong Lin; Wu-Juan Hao; Ren-Min Zhou; Cui-Lan Huang; Xu-Yang Wang; Yan-Shan Liu; Xiao-Zhong Li (Frontiers in Microbiology, 2023)
ObjectivesInflammatory bowel disease (IBD) is a chronic lifelong inflammatory disease. Probiotics such as Bifidobacterium longum are considered to be beneficial to the recovery of intestinal inflammation by interaction with gut microbiota. Our goals were to define the effect of the exclusive use of BAA2573 on dextran sulfate sodium (DSS)-induced colitis, including improvement of symptoms, alleviation of histopathological damage, and modulation of gut microbiota.MethodsIn the present study, we pretreated C57BL/6J mice with Bifidobacterium longum BAA2573, one of the main components in an over-the-counter (OTC) probiotic mixture BIFOTO capsule, before modeling with DSS. 16S rDNA sequencing and liquid chromatography–tandem mass spectrometry (LC-MS/MS)-based non-targeted metabolomic profiling were performed with the collected feces.ResultsWe found that pretreatment of Bifidobacterium longum BAA2573 given by gavage significantly improved symptoms and histopathological damage in DSS-induced colitis mice. After the BAA2573 intervention, 57 genera and 39 metabolites were significantly altered. Pathway enrichment analysis demonstrated that starch and sucrose metabolism, vitamin B6 metabolism, and sphingolipid metabolism may contribute to ameliorating colitis. Moreover, we revealed that the gut microbiome and metabolites were interrelated in the BAA2573 intervention group, while Alistipes was the core genus.ConclusionOur study demonstrates the impact of BAA2573 on the gut microbiota and reveals a possible novel adjuvant therapy for IBD patients.